Effect of Stocking Density on Seaweed Production (Kappaphycus alvarezii) Rearing With Hanging Rope Method - Rosdiana '; Usman Muhammad Tang; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted from 17 March until 28 April 2014 in the waters of Hamlet Village Sugie Subdistrict Moro Karimun District of Riau Islands province. The method used is an experimental with 1 factors and five level of treatment and 3 replications. 1 meter rope tied with 100 g of seaweed seed with different space of 10 cm, 15 cm, 20 cm, 25 cm and 30 cm respectively. Data were analyzed using ANAVA (P<0.05). Based on the findings that the was best of (Kappaphycus alvarezii) on density with the specific growth rate highest of 30 cm was (766.67 g/clump; 4.99%) and the lowest density of 10 cm with an average weight (212 g/clump; 1.80%). while the highest dried seaweed production was in the treatment of 15 cm with a dry weight of 370.42 g/ hanging rope and the lowest of 10 cm with a weight of dry production 265 g/ hanging rope.Keyword : K. alvarezii, Seaweed Production, Hanging Rope Method, Growth, Karimun